CMV retinitis in an HIV patient with clinical and immunological failure on HAART - Dipankar Chakraborty; Samir Kumar Rama (Universiti Kebangsaan Malaysia, 2015)
Cytomegalovirus (CMV) retinitis is a complication of patients infected with human immunodeficiency virus (HIV) in advance stage when CD4 count is less than 50 cells/cumm. Before the introduction of highly active antiretroviral therapy (HAART), approximately 30% of patients with AIDS developed CMV retinitis, which declined in 75% of cases after the start of HAART. We report a case of CMV retinitis in an HIV-positive patient who developed it as a WHO clinical stage 4 condition representing clinical failure along with dramatic decrease in CD4 count due to immunological failure on failing first-line HAART.